What drives the perceived legitimacy of collaborative governance? An experimental study - LEE, Seulki (Institutional Knowledge at Singapore Management University, 2023)
This study explores the perceived legitimacy of collaborative governance from a citizens’ perspective. We use a preregistered online survey experiment to test the effect of three factors—representation, performance information, and issue complexity—on the perceived legitimacy of a collaboration. Findings from 1,470 U.S. respondents show that representation and positive performance information influence citizens’ perceptions of collaborative governance legitimacy, while issue complexity has little impact. Additionally, heterogeneous treatment effects were found: respondents with low trust in public organizations factor representation more into their legitimacy perceptions of collaborative governance, while those with high trust in public organizations show little influence of representation.